Applying the nominal group technique to determine emerging stressors related to youth mental health: findings from a multi-country stakeholder consensus-building exercise - Isaacs, Nazeema; Essack, Zaynab; Mutengu, Lilian; Wawire, Salome; Gichoga, Susan; Neba, Alphonsus; Alam, Uzma; Mabia, Constance; Sekhejane, Palesa; Bitanihirwe, Byron (Frontiers in Psychiatry, 2025)
BackroundYouth represents a distinct phase of neurodevelopment encapsulating a unique mix of personal, social, and environmental stressors that can impact mental health and increase vulnerability to mental illness. To gain a cross-national understanding of the stressors that may impact young people’s mental wellbeing, we conducted a consensus-building exercise focused on ranking a list of stressors that emerged through stakeholder deliberation.MethodsWe adopted the nominal group technique (NGT) as an exercise to reach a consensus among representatives from 11 low- and middle-income countries (spanning Africa, Asia, Europe, and Latin America) in terms of stressors linked to young people’s mental wellbeing. A single session of NGT was applied to probe what country representatives felt were the most pressing stressors associated with youth mental health in the context of the relational wellbeing model (at the personal, social, and environmental levels).ResultsRepresentatives identified 18 stressors—that included mental health awareness, media, stigma, climate change and policy, among others—as being high priority for developing research geared towards youth mental health.ConclusionThere was a high level of consensus in terms of the stressors that were identified in relation to youth mental health, suggesting that use of NGT provides an effective tool to generate pertinent data from a single session with important research and policy implications. These findings underscore the need for more empirical research focused on knowledge gaps associated with the identified stressors—in terms of youth mental health—which can then better inform funding agendas as well as mental health policy and practice.